Investigating Food Quality at UUM’s Lake Restaurant: Are Customers Satisfied? - Ideris, Muhamad Shah Kamal; Mustafa, Eshaby; Saadin, Muhamad Nizam (UUM Press, 2021)
The restaurant concept plays an important role in establishing and running a successful food business. Maintaining the quality of foods is an important criterion that service providers must look at to attract new customers and retain existing customers on the premises. By considering the importance of the quality of foods and customers in the restaurant industry, this study examines the relationship between the quality of food attributes and customer satisfaction. The research utilized a quantitative approach to conducting the study. Universiti Utara Malaysia students who visited The Lake restaurant are chosen as the unit of analysis. The close-ended questionnaires were distributed to the students to obtain the data for this study. In order to conduct the survey, the researchers used Google form as a tool. The questionnaires were distributed by Google form using the purposive sampling method. A total of 400 questionnaires were distributed among the students, and 364 usable questionnaires proceeded for the descriptive and inferential analyses of the study. The study found that there is a positive relationship between food quality attributes (freshness, taste, healthy options, variety of menu, presentations, and temperature) and customers' satisfaction. The findings of the study posed significance and added new knowledge to the practitioners and academicians.